Scale Based Age and Growth Analysis of Exotic Fish Tilapia (Oreochromis mossambicus P 1852) in Vallabhsagar Reservoir, Gujarat, India - Ujjania, N. C.; Shah, Niharika P.; Prajapati, S. D.; Padvi, Divya G. (International Journal of Bio-resource and Stress Management, 2023)
The current study was conducted during post monsoon season (November, 2021–April, 2022) and 505 tilapia scales were randomly collected from the commercial fish collection centers i.e. Naranpur, Nesu Vadpada and Rumkitalav of Vallabhsagar reservoir, Gujarat, India. Fish scales described the age and growth of tropical conditions that provided detailed facts about their life history, ecology and habitat of fish which help to manage the water body for optimum fish production. The result showed that age of tilapia ranged from 1+ to 5+ year with total length 15.000–33.700±23.598 cm and weight 77.000–662.000±309.951 g. The calculated length (cm) of the back was 8.80, 14.758, 21.612, 26.170 and 28.846 cm while body weight (g) 17.690, 76.171, 223.369, 386.865 and 506.744 g were noted for 5 age classes respectively. The average specific size (5.77) and the index of population weight growth intensity (157.00) were observed whereas specific rate of linear growth (Cl) and specific rate of weight increase (Cw) were decreasing with increase in age. The growth constant average (Clt(Ave)) shows two growth phases, i.e. 0.67 and 0.22. The findings of current study help to conclude that the aquatic environment of Vallabhsagar reservoir was suitable to harbour these fishes and was conducive for satisfactory growth and wellbeing of tilapia. Results of the study provided baseline information which would be helpful for the scientific management of Tilapia fisheries in the Vallabhsagar Reservoir in Gujarat.